Evidence-based summary of preventive care for central venous access device-related thrombosis in hospitalized children - Lingyun Tian; Xinyu Feng; Hui Luo; Weijuan Li; Mengyuan Liu; Jing Jiang; Yinglan Li (BMC, 2024)
Abstract Purpose This study aims to summarize the latest and best evidence on central venous access device-related thrombosis (CRT) in hospitalized children, which provides theoretical support for standardizing the preventive care practice of CRT in hospitalized children. Methods Relevant guidelines, systematic reviews and expert consensuses were reviewed through ten guideline websites, six professional association websites and seven databases. The literature evaluation was conducted, and the best evidence from qualified studies was extracted and summarized. Furthermore, the best evidence was summarized through expert consultation and localized for the preventive care practice of CRT in hospitalized children in China. Results A total of 14 topics and 68 best evidence were collected, including personnel qualification and quality management, pediatric patient selection, risk assessment, central venous access device (CVAD) selection and use, tip position, catheter maintenance, basic prevention, drug prevention, imaging examination, health education, nursing records, follow-up, CVAD removal and others. Conclusion In this study, the best evidence based on evidence-based nursing was summarized, and expert consultation was adopted to localize the best evidence collected. It is of great significance to standardize the clinical practice of pediatric nurses and ensure the effectiveness of CRT preventive care for hospitalized children, thus guaranteeing the safety of hospitalized children with CVAD catheterization.